Simulation optimization of lean production strategy by considering resilience engineering in a production system with maintenance policies. (January 2017) - Zarrin, Mansour; Azadeh, Ali
Lean production aims are to reduce work-in-process and maintain close to zero inventories and resilience is about reacting quickly to disruptions impacting manufacturing systems. In this study, a manufacturing organization with maintenance strategy is simulated to evaluate the impacts of resilience engineering (RE) principles on lean practices. The process of simulation is conducted for different scenarios. Each scenario includes a set of resilience principles. Using computer simulation, many outputs are calculated namely, utility and availability of machines and maintenance operators, time in system, total cost, and number of failures. The optimal values of scenarios' efficiencies are achieved using data envelopment analysis (DEA) model, which is a mathematical programming approach. The results of the DEA are validated by using principal component analysis. In addition, an analysis is performed to determine which factor of RE has the maximum effect on the system's performance. The results show that the redundancy among the RE principles, has the maximum impact on the system's performance. To the best of my knowledge, this is the first study that evaluates the performance of lean production considering RE in a production line with maintenance policies.